(3GdHMK GdYdej eagheg hCOhGJg hCSGdjHg (B/s - (3PhbGf, YHjOGJs; (3YOS, YHO GdQMeGfs; (3cGjO, YHO GdMbs ((3YeGf(B: s (3OGQ GdacQ ddfTQ hGdJhRjY(B, s, 2005)
(3GdYde hGdHMK GdYdej(B-(3CSGSjGJ GdHMK GdYdej(B-(3COhGJ GdHMK GdYdej(B-(3CSGdjH GdHMK(B-(3cJGHI GdHMKs
Keywords: (3CSGdjH GdHMK GdYdejs; (3HMK Ydejs; (3Ydes